ANALISIS FRAMING PEMBERITAAN MEDIA ONLINE DETIK.COM DAN KOMPAS.COM PADA PROYEK PEMBANGUNAN IKN PERIODE 1-7 NOVEMBER - anshori, syukron; Apriandani, Hendri; Suprapto, Deddy (ROLLING, 2024)
This study aims to analyze the framing of online media Detik.com and Kompas.com related to the development of the Nusantara Capital Project (IKN) in the period 1-7 November 2023. The method used is framing analysis using Zhongdang Pan and Gerald M models. Kosicki, which consists of four main structures: syntactic, script, thematic, and rhetorical. This study identifies how the two media frame news about IKN development, including news focus, word choice, and information presentation. The results of the analysis show that there are differences in the way the two media deliver news, which is influenced by the editorial policies and objectives of each media. Detik.com tends to place more emphasis on the technical aspects and physical achievements of development, while Kompas.com more on the political and social issues related to the project. The research provides insight into how media shape public perception through their framing strategies.